HIGH SECONDARY STAGE PRINCIPALS AND THEIR ABILITY OF PROCESSING EDUCATIONAL RESEARCH SKILLS FROM THEIR PERSPECTIVE IN JORDAN - Al- Ali, Yousra (European Scientific Journal, ESJ, 2013)
This study aimed at investigating the ability extent of high secondary school principals in processing education research from their point of view in Jordon. In addition the differences between teachers having such skills due to gender , education level, school administration experience. The involved study sample consisted of (254) males and females principals distributed on three education directorates belonged to the Jordanian Ministry of Education. To answer the research objectives the researcher developed a questionnaire of (73) items SPSS was used to analyze the data. In addition descriptive analysis were used to find the frequencies and percentage for identifying sample’s characteristics. Means and standard deviations of subject responses were computes . One way ANOVA and ( T ) test have been used. The study concluded the following result , means indicated that secondary school principals have , to a great extent , the skills for educational research . Results also revealed that there are statistical differences between the study sample averages due to gender in favor of males and there aren’t any statistical differences related to scientific qualification , school administration experience . In conclusion the researcher recommends more specialized courses to be held for male and female principals on the basic skills of educational research in order to make use of them in the school administration process.